2015
DOI: 10.4049/jimmunol.1402690
|View full text |Cite
|
Sign up to set email alerts
|

TLR7- and TLR9-Responsive Human B Cells Share Phenotypic and Genetic Characteristics

Abstract: B cells activated by nucleic-acid sensing Toll-like receptor 7 and TLR9 proliferate and secrete immune globulins. Memory B cells are presumably more responsive due to higher TLR expression levels, but selectivity and differential outcomes remain largely unknown. In this study, peripheral blood human B cells were stimulated by TLR7 or TLR9 ligands, with or without IFNα, and compared to activators CD40L plus IL-21, to identify differentially responsive cell populations, defined phenotypically and by BCR characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 65 publications
2
31
2
Order By: Relevance
“…C). Together, these data are in line with observations of other groups showing that TLR9 (CpG‐B) stimulation mainly expands CD27 + IgM memory B cells …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…C). Together, these data are in line with observations of other groups showing that TLR9 (CpG‐B) stimulation mainly expands CD27 + IgM memory B cells …”
Section: Resultssupporting
confidence: 92%
“…In cultures stimulated with CpG‐B, we observed a general increase in the frequency of CD27 + B cells and the occurrence of cells expressing high levels of CD27. This population is regarded to represent cells committed to the plasma cell lineage . Proliferation (dilution of the dye PKH26) was observed in CD27 low cells, but was particularly pronounced in CD27 high cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that a TLR7 polymorphism is highly associated with human SLE (Wang et al, 2014;Tian et al, 2012). However, our previous and current data indicate that the conjugate did not show any ability to induce in vitro proliferation of human or murine B cells, while to the contrary other endosomal TLR7 or TLR9 ligands such as imidazoquinolines or CpG-ODNs did (Simchoni and Cunningham-Rundles, 2015). It is generally agreed that molecular structure, local amount, affinity for the receptors and time of the interaction may affect the quality and intensity of signals exerted by different ligands of the same TLR agonists: this could explain potential differences between the effects of modified adenines and other TLR7 ligands (Chang, 2010).…”
Section: Discussioncontrasting
confidence: 72%
“…TLR7 stimulation was associated with increased expression of Blimp-1, the master regulator of ASC differentiation as well as AID, the enzyme required for class switching and somatic hypermutation [23]. Studies using human B cells similarly reported a role for TLR7 in promoting differentiation into ASC [24, 25]. If R848 is promoting differentiation into ASC, it does not appear to be at the expense of memory B cell generation.…”
Section: Discussionmentioning
confidence: 99%